EVALUATION OF BILE TOLERANCE IN DAIRY AND HUMAN ORIGIN LACTOBACILLUS FERMENTUM STRAINS - Behare, Pradip Vishnu; Panicker, Aiswarya Saidharan (Indian Journal of Dairy Science, 2014)
Eleven Lactobacillus fermentum strains including seven dairy and four faecal origin were studied for in vitro bile tolerance at 0, 0.3, 0.6, 0.9, 1.2, 1.5 and 1.8 % bile concentration to assess their probiotic potential. At 0.3 and 0.6% bile concentration except NCDC-400, all dairy origin strains shown 3 to 5 log reduction in count, while faecal origin strains did not show much reduction. Almost similar trend was observed for dairy strains at 1.2 to 1.5 % bile concentration whereas BIF-18, BIF, 19 and BIF 20 from faecal strains shown better growth. Lactobacillus fermentum BIF-19 from faecal and Lactobacillus fermentum NCDC-400 from dairy origin were most bile tolerant. Out of all strains BIF-19 exhibited highest survival in all concentration of bile.